Dampak Temporal dan Spasial Pembangunan Industri Di Desa Tanjungrejo, Kecamatan Wirosari, Kabupaten Grobogan - Aliyah, Janatin; Setiadi, Rukuh (Jurusan Perencanaan Wilayah dan Kota, 2024)
This study investigates the development of industry which is located in a rural area setting. It quite contradicts the mainstream phenomena where most industries try to maintain their proximity to major cities. Although Grobogan Regency is an example of an administrative region dominated by rural areas, its industrial sector has become the largest contributors of the regional GDP. The existence of a large scale industry in Tanjungrejo Village, Grobogan Regency may explain this regional economic tendency. Other than its economic impacts, lack of study focusing on other dimension of impacts of such industries. Therefore this paper aims to understand the impact of the large scale industry in Tanjungrejo, Wirosari, Grobogan particularly from temporal and spatial point of views. This study employs quasi experiment with a primary questionnaire data collected through random sampling survey as well as semi-structured interview in the study area and another controlled village. Additionally, the secondary data sources of this study include document review and utilization of open data maps. This study uses descriptive analysis to provide an explanation of the temporal-spatial impact of each variable (i.e. land use and social changes). The results shows that industrial development in the village has impacts on the increasing availability of facilities, income and employment, while its social impacts are less significant.